Appropriateness and preferential use of different seasonal influenza vaccines: A pilot study on the opinion of vaccinating physicians in Italy. Issue 7 (8th February 2019) - Boccalini, S.; Tacconi, F. Mandò; Lai, Piero Luigi; Bechini, A.; Bonanni, P.; Panatto, D.
Abstract: In Italy, several types of influenza vaccine are on the market. Available evidence suggests that no single vaccine type is universally appropriate; rather, different types may be more appropriate for different population strata. However, while the concept of appropriateness/preferential use of single vaccines is usually adopted at the central level, little is known about the attitudes of physicians on the matter. A pilot survey of Italian physicians ( N = 372) revealed that most (about 90%) were aware that the available vaccines were different, and that particular vaccines were more appropriate for specific groups. The availability of explicit guidelines on which vaccine to administer to a given population group was deemed desirable by 93.2% of respondents. The results were consistent with the 2018 Italian and UK normative documents, which indicate adjuvanted vaccines as the most appropriate choice for the elderly, and quadrivalent formulations for the younger age-classes. Public health policy implications are discussed.